Alcohol-Related Mortality in the WHO European Region: Sex-Specific Trends and Predictions. (4th September 2019) - Pruckner, Nathalie; Hinterbuchinger, Barbara; Fellinger, Matthäus; König, Daniel; Waldhoer, Thomas; Lesch, Otto M; Gmeiner, Andrea; Vyssoki, Sandra; Vyssoki, Benjamin
Abstract: Aims: Alcohol is an important risk factor for morbidity and mortality, especially within the European region. Differences in per capita consumption and drinking patterns are possible reasons for regional differences and diverging trends in alcohol-related health outcomes. Methods: Twenty-nine countries within the World Health Organization (WHO) European region were evaluated for trends and predictions in alcohol-related deaths within the last four decades using data available from the WHO Health for All database. Results: Between 1979 and 2015, age-standardised death rates due to selected alcohol-related causes decreased significantly for both sexes in all assessed countries of the WHO European region, but regional differences are still pronounced. Assuming a similar trend in the future, the model predicted a further decrease until the year 2030. Conclusion: Even though alcohol-related mortality may have decreased within the last decades, the detrimental effects of alcohol consumption and alcohol dependence remain a considerable burden of disease within Europe. Abstract : Short Summary According to data from the WHO Health for All database, alcohol-related deaths have significantly decreased within the European region between 1979 and 2015 and are predicted to further decline. Yet, there are still marked differences between regions and burden of alcohol consumption and dependence remains high.